Simultaneous Photoelectrocatalytic Oxidation and Nitrite‐Ammonia Conversion with Artificial Photoelectrochemistry Cells. Issue 48 (6th November 2022) - Song, Yurou; Wu, Yunzhen; Cao, Shuyan; Zhang, Yanxue; Luo, Degen; Gao, Junfeng; Li, Zhuwei; Sun, Licheng; Hou, Jungang
Abstract: Artificial photoelectrochemistry system harvests solar energy for solar fuel conversion by use of semiconductor anode and cathode. However, the low overall performance of this integrated system is limited by the compatibility and durability. Herein, a compact heterostructure photoanode exhibits >98% selective photoelectrocatalytic oxidation conversion and >99% Faradaic efficiency of benzyl alcohol oxidation at 0.67 V versus reversible hydrogen electrode in comparison of single‐phase photoanodes. Density functional theory calculations reveal the heterointerface is responsible for the appreciable electronic interaction and the accelerated charge transport, exploring the radical relay pathway as the selective oxidation mechanism. Especially, the integrated photoelectrochemistry cell is developed by heterostructure photoanode and protective photocathode, simultaneously enabling the efficient photoelectrocatalytic oxidation conversion and nitrite reduction reaction to ammonia synthesis under ambient conditions with a maximum Faradaic efficiency >98%. This work sheds light on rational design and the construction of artificial photoelectrochemistry cells towards solar energy conversion. Abstract : The integrated artificial photoelectrochemistry cell is developed by CdS/CdIn2 S4 photoanode and protective Cu2 O photocathode, simultaneously enabling the efficient conversion of benzyl alcohol to benzaldehyde and nitrite reduction reaction to ammonia synthesis under ambient conditions.